2021
DOI: 10.1186/s12954-020-00449-1
|View full text |Cite
|
Sign up to set email alerts
|

“Running myself ragged”: stressors faced by peer workers in overdose response settings

Abstract: Background Peer workers or “peers” (workers with past or present drug use experience) are at the forefront of overdose response initiatives, and their role is essential in creating safe spaces for people who use drugs (PWUD). Working in overdose response settings has benefits for peer workers but is also stressful, with lasting emotional and mental health effects. Yet, little is known about the stressors peer workers face and what interventions can be implemented to support them in their roles.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 73 publications
1
49
0
Order By: Relevance
“…Despite the benefits of peer-based service work, there is consistent evidence of challenges to hiring peers within organizations [ 21 ]. Peer workers face a disproportionate amount of pressure, burden, and trauma in their work, especially in overdose prevention contexts [ 17 , 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the benefits of peer-based service work, there is consistent evidence of challenges to hiring peers within organizations [ 21 ]. Peer workers face a disproportionate amount of pressure, burden, and trauma in their work, especially in overdose prevention contexts [ 17 , 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peer workers face a disproportionate amount of pressure, burden, and trauma in their work, especially in overdose prevention contexts [17,20,22]. Studies also show that peer workers receive minimal social and emotional supports [17,[20][21][22], which may be partially attributable to their casual work arrangements [23]. Questions are being raised about the sustainability or potential burnout of the peer workforce, especially in the context of the overdose crisis in North America [21,23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer workers indicated that their work is stressful and despite their wholehearted commitment to the job (36, 37), their lack of organizational and mental health supports to mitigate their stresses creates notable dissatisfaction. Lack of such resources often led to low morale and burnout (37).…”
Section: Organizational Supportmentioning
confidence: 99%
“…Step 1: Needs Assessment Eight focus groups with 31 participants in total were conducted between November 2018 and March 2019; two in the Fraser region, two in Vancouver and four in Victoria. Details on recruitment of participants, interview processes, and data analysis are described in two previously-published articles (36,37).…”
Section: Designing the Modelmentioning
confidence: 99%